The Future of Fashion: How the Quest for Digitization and the Use of Artificial Intelligence and Extended Reality Will Reshape the Fashion Industry After COVID-19 - Silvestri, Barbara (ZoneModa Journal, 2020)
The aim of this paper is to analyze how extended reality (formed by virtual and augmented reality), and artificial intelligence are influencing the fashion field. During and after the Covid19 pandemic, a radical shift happened: most activities, from shopping to showrooms and fashion weeks had to move online. While e-commerce was already a consolidated pillar of fashion shopping, it recently started to evolve to achieve through AR (augmented reality) and VR (virtual reality) what customers could before find in physical stores: interesting experiences and sensory stimuli. Online traffic peaked, creating even more room for technology based on artificial intelligence. With its disrupting powers, AI (artificial intelligence) has all the potentialities to take over each step of the fashion value chain. Furthermore, with the quarantine the production of fashion was slowed down by the absence of workers in production sites. Artificial intelligence and automation could be an answer. In this paper AR, VR and AI technologies are analyzed with practical examples on what has happened and is happening in the industry, from a perspective based on the challenges imposed by Covid-19. Results indicate that AR, VR and AI have the potential to become in the near future the norm in the fashion media and technology ecosystem, reinforcing the digitization process of the industry.